THE EFFECT OF PROJECT BASED LEARNING AND LEARNER AUTONOMY ON STUDENTS’ SPEAKING SKILLS - Setia Dewi, Kadek Mirah (LPPM Undiksha, 2020)
This study was aimed at investigating the effect of project-based learning on students? speaking skills at the eighth grade students of SMPN 5 Kuta Selatan in academic year 2018/2019. The design of the study was post-test only control group with 2x2 factorial designs. Sample involved 82 students that were selected through random sampling technique. The data were collected through questionnaire of learner autonomy and speaking performance test which had been validated before. The data were analysed by using two way ANOVA and t-Scheffe. The study discovered: there was different effect in speaking skills between the students who were taught by using project-based learning and those who were taught by using conventional method (F=18.391 and p<0.05) in which the Project-Based Learning group excelled better in speaking skills, there was an interaction between learner autonomy and project-based learning in affecting students? speaking skills (F= 45.325 and p<0.05), the students in which high learner autonomy who were taught by using the project-based learning affect better than those who were taught by using conventional method; however, there was not significantly different in speaking skills of the students with low learner autonomy who were taught by using project-based learning and who were taught by using conventional method (p>0.05).